2022
DOI: 10.1093/mnras/stac2003
|View full text |Cite
|
Sign up to set email alerts
|

Hidden cooling flows in clusters of galaxies

Abstract: The radiative cooling time of the hot gas at the centres of cool cores in clusters of galaxies drops down to 10 million years and below. The observed mass cooling rate of such gas is very low, suggesting that AGN feedback is very tightly balanced or that the soft X-ray emission from cooling is somehow hidden from view. We use an intrinsic absorption model in which the cooling and coolest gas are closely interleaved to search for hidden cooling flows in the Centaurus, Perseus and A1835 clusters of galaxies. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 110 publications
0
25
0
Order By: Relevance
“…We showed in HCFI (Fabian et al 2022) that, under the high pressure conditions of an HCF (𝑛𝑇 ∌ 10 6.5 − 10 7.5 cm −3 K ) and no heating, the gas cools rapidly (timescale of tens of years) to ∌ 3đŸ. The Jeans mass is below about 0.1 M ⊙ (Jura 1977;Ferland et al 1994) and the gas expected to clump and fragment into low mass stars, brown dwarfs etc, some of which will fall into the black hole emitting little radiation.…”
Section: Accretion Of Fragmented Cold Matter By the Central Black Holementioning
confidence: 78%
See 1 more Smart Citation
“…We showed in HCFI (Fabian et al 2022) that, under the high pressure conditions of an HCF (𝑛𝑇 ∌ 10 6.5 − 10 7.5 cm −3 K ) and no heating, the gas cools rapidly (timescale of tens of years) to ∌ 3đŸ. The Jeans mass is below about 0.1 M ⊙ (Jura 1977;Ferland et al 1994) and the gas expected to clump and fragment into low mass stars, brown dwarfs etc, some of which will fall into the black hole emitting little radiation.…”
Section: Accretion Of Fragmented Cold Matter By the Central Black Holementioning
confidence: 78%
“…We have recently found Hidden Cooling Flows in clusters and groups of galaxies, as well as a couple of nearby elliptical galaxies (HCFI and HCFII) (Fabian et al 2022(Fabian et al , 2023, using spectra from the XMM Reflection Grating Spectrometer (RGS). These soft X-ray-emitting flows are hidden within photoelectrically-absorbing cold clouds and dust near the centres of the central brightest galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent works reported the discovery of hidden cooling flows in a sample of nearby clusters of galaxies, including Perseus (see Fabian et al 2022Fabian et al , 2023aFabian et al , 2023b. Here, the authors argue that AGN feedback may not be as efficient in heating the ICM as initially thought; instead, the ICM would be allowed to cool, explaining the substantial molecular gas reservoirs found in these systems.…”
Section: Extended Filaments and Turbulent Radiative Mixing Layersmentioning
confidence: 90%
“…Indeed, extreme cooling of the gaseous material surrounding BCGs could prohibit them from being detected due to extremely low temperature and emissivity (see Fabian et al 2023a). According to these results, cooling flows of ∌30-100 M e yr −1 could therefore be present within clusters such as the Perseus cluster of galaxies (Fabian et al 2022). Interestingly, it is suggested that these hidden cooling flows could have internal structures resembling that of turbulent radiative mixing layers, similar to those proposed here (see Begelman & Fabian 1990;Fabian et al 2023a).…”
Section: Extended Filaments and Turbulent Radiative Mixing Layersmentioning
confidence: 98%
“…It may also become sufficiently dense to become optically thick and hence also be affected by coupling to radiation (see Proga et al, 2022). Optically thick gas might be better detected in absorption (unless irradiated) and hence the multiphase medium in the cluster core can be possibly revealed better by considering emission, absorption, and re-emission (e.g., Fabian et al, 2022). There is no systematic theoretical study of the formation of optically thick gas in the diffuse ICM/CGM for the lack of sufficient observational evidence.…”
Section: Thermal Instability In the Icmmentioning
confidence: 99%